An Audio-Visual Approach to Measuring Discourse Synchrony in Multimodal Conversation Data - CAMPBELL, NICK (ISCA, 2009)
This paper describes recent work on the automatic extraction of visual and audio parameters relating to the detection of synchrony in discourse, and to the modelling of active listening for advanced speech technology. It reports findings based on image processing that reliably identify the strong entrainment between members of a group conversation, and describes techniques for the extraction and analysis of such information.
PUBLISHED
Keywords: discourse interaction; active listening; image and audio processing; conversation